Investigations on wire electric discharge machining of hybrid nano metal matrix composites (AA6061/SiC/B4C) for industry need based multi-response optimization. (14th November 2019) - Das, Shubhajit; Chandrasekaran, M; Samanta, S
Abstract: The present experimental investigation is aimed at selecting the best suitable machining combination for wire electric discharge machining (WEDM) of AA6061 reinforced with 1.5 wt% SiC and 1.5 wt% B4 C ceramic nano particles. The WEDM experiments were planned based on central composite design by considering flow rate ( FR ) of the dielectric, servo voltage ( SV ), pulse off time ( T off ) and pulse on time ( T on ) as the input variables to investigate on material removal rate ( MRR ) and surface roughness ( R a ). The signal to noise ( S/N ) ratios was used to identify the influencing parameters on maximizing MRR and minimizing R a . The combination of factors was found as A5-B1-C1-D1 ( T on : 1.35 μ s, T off : 120 μ s, SV : 35 V, FR : 4 l min −1 ) for MRR and A2-B1-C5-D4 ( T on : 1.05 μ s, T off : 120 μ s, SV : 75 V, FR : 7 l min −1 ) for R a respectively. The output responses were modeled using response surface methodology (RSM) and were used for multi-objective optimization using Pareto optimality approach. The proposed 18 Pareto optimal solutions can be used for job floor applications in industries for optimum machining of this hybrid nano composites. The field emission scanning electron microscopy (FESEM) analysis of the WEDM machined surfaces shows the presence of wider and deeper craters, micro voids and lumps of debris leading to higher material removal rate.